PENGARUH PERSEPSI MAHASISWA AKUNTANSI TENTANG PAJAK, PENGHARGAAN FINANSIAL, DAN MOTIVASI TERHADAP MINAT BERKAIR DI BIDANG PERPAJAKAN: (Studi Kasus Pada Mahasiswa Program Studi S-1 Akutnansi di Kota Semarang) - Subagio, Indra Sukma; Cicilia Agnes Utomo (LPPM Universitas Harapan Bangsa, 2024)
The purpose of this study was to determine the effect of perceptions, financial rewards, and motivation on interest in a career in the field of taxation either partially or simultaneously. This research was conducted at the Accounting Study Program in Semarang City. The sampling technique in this study used a purposive sampling technique. The total population is 7,162 students and 99 students are taken as research samples. The results of this study indicate that perceptions and financial rewards influence career interest in taxation. Motivation does not affect career choices in taxation. Perceptions, financial rewards, and motivation simultaneously influence career choices in the field of taxation.